1993
DOI: 10.1203/00006450-199309000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Priming Activity of Newborn Cord Blood–Derived Polymorphonuclear Neutrophilic Granulocytes with Lipopolysaccharide and Tumor Necrosis Factor-α Triggered with Formyl-Methionyl-Leucyl-Phenylalanine

Abstract: ABSTRACT. Newborn infants are more susceptible to bacterial infections than adults. This susceptibility has been attributed to defects in humoral and cellular activity. Host cellular activity can be modified by factors produced by bacteria or the host in response to infection. We assessed the effect of two factors associated with gramnegative bacterial infection, lipopolysaccharide (LPS) and TNF-a, on polymorphonuclear neutrophilic granulocytes (PMN) obtained from adult or newborns (umbilical cord blood). PILI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…Labor is associated with the generation of inflammatory cytokines, including IL-6 and IL-8, which are known to stimulate the production of ROIs in neutrophils (33). These findings are consistent with previous reports that the oxidative response to inflammatory mediators is impaired in term neonatal neutrophils (34,35). Decreased responsiveness to inflammatory stimuli may be related to defects in the activation of signaling via the nuclear transcription factors STAT-1 and NF-B in neonatal cells (36).…”
Section: Discussionsupporting
confidence: 89%
“…Labor is associated with the generation of inflammatory cytokines, including IL-6 and IL-8, which are known to stimulate the production of ROIs in neutrophils (33). These findings are consistent with previous reports that the oxidative response to inflammatory mediators is impaired in term neonatal neutrophils (34,35). Decreased responsiveness to inflammatory stimuli may be related to defects in the activation of signaling via the nuclear transcription factors STAT-1 and NF-B in neonatal cells (36).…”
Section: Discussionsupporting
confidence: 89%
“…We have shown previously that PMNs from newborns are primed less effectively in vitro with LPS compared to PMNs from adults (7,38). Similarly, some authors have found that monocytes from newborns have a lower response than adult monocytes in the secretion of cytokines, such as TNF-␣, after LPS stimulation (11,36).…”
mentioning
confidence: 93%
“…Although neutrophils from newborns exhibit defects in chemotaxis, phagocytosis, and oxidative metabolism (1)(2)(3)(4), infants are at high risk for neutrophil-mediated tissue injury. Activated neutrophils are cleared from inflamed sites by the process of apoptosis, followed by macrophage phagocytosis.…”
mentioning
confidence: 99%